2020
DOI: 10.1016/j.frl.2020.101717
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and investor behavior

Abstract: Highlights We investigate trading patterns of retail investors during the outbreak of COVID-19. Investors increase their weekly trading intensity and establish more new positions. Investors add funds to their accounts and open more new accounts. Investors significantly reduce the usage of leverage. Investors marginally increase their tendency to engage in short selling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
98
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(108 citation statements)
references
References 18 publications
8
98
1
1
Order By: Relevance
“…Studying each sector separately can take care of the sector specific factors. Though many studies (Liu et al, 2020b;Mirza et al, 2020) apply event study approach to COVID-19 research, this paper applies OLS regression in line with Ortmann et al (2020) to analyse the impact of COVID-19 on stock market over a period of months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying each sector separately can take care of the sector specific factors. Though many studies (Liu et al, 2020b;Mirza et al, 2020) apply event study approach to COVID-19 research, this paper applies OLS regression in line with Ortmann et al (2020) to analyse the impact of COVID-19 on stock market over a period of months.…”
Section: Methodsmentioning
confidence: 99%
“…Using different measures representing the COVID-19 pandemic, Alber (2020) investigated how the stock markets of six worst affected countries react to the pandemic, and the results indicate that stock market return showed more sensitivity to coronavirus cases rather than deaths while also being more impacted by cumulative cases than the new ones. On a different note, Ortmann et al (2020) focused on retail investor reaction to the COVID-19 pandemic. Regression analysis exposes that when the number of COVID-19 cases doubled, the trading intensity of investors jumped by 13.9%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature in capturing the COVID-19 fear and investor behavior are very few. Ortmann et al (2020) used transactional level brokerage data of retail investors to analyze the investor behavior during COVID-19 times. Their study found that investors reduced the usage of leverage and increased their weekly trading intensity during COVID-19 times.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As regards investing strategies over the SARS-CoV-2 crisis, Ortmann, et al [71] suggested that investors open more stock and index positions, but do not shift to safe-haven or perilous investments. Hence, Cheema, Faff and Szulczyk [20], Cheema, Faff and Szulczyk [21] advised that gold and silver lost momentum in favor of liquid and stable assets such as treasuries and the Swiss franc.…”
Section: Prior Research Regarding the Economic And Financial Consequementioning
confidence: 99%